1984
DOI: 10.1099/00222615-18-1-47
|View full text |Cite
|
Sign up to set email alerts
|

Vaginal carriage and neonatal acquisition of Clostridium difficile

Abstract: SUMMARY. The relationship between vaginal carriage and subsequent neonatal acquisition of Clostridium dzficile was investigated. Vaginal carriage of C. dzficile was detected in 11% of women attending the Department of Genital Medicine Clinic. C. dzficile was isolated from the vagina in 18% of 50 mothers before delivery, and 8% after delivery; 62% of their babies had positive faecal cultures. Eight of nine of the babies whose mothers had positive cultures before delivery became colonised with C. dzficile, while… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

1988
1988
2016
2016

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 27 publications
(10 citation statements)
references
References 12 publications
0
10
0
Order By: Relevance
“…38°C) in 26 to 66% of patients (102,196,262). Leukocytosis is a common clinical feature in the severely ill patient, with leukocyte counts exceeding 15,000 cells per mm3 in 40 to 50% of patients (196,262 (34,35,73,118,153,178,228,252,258); however, other studies have reported acquisition rates of 0 to 6% (127,153,246,257). These differences in the acquisition rates of C. difficile in neonates and young children most likely represent varied degrees of environmental exposure in nurseries or transfer from the hands of hospital staff rather than disparities in the rate of maternal exposure (12).…”
Section: Introductionmentioning
confidence: 99%
“…38°C) in 26 to 66% of patients (102,196,262). Leukocytosis is a common clinical feature in the severely ill patient, with leukocyte counts exceeding 15,000 cells per mm3 in 40 to 50% of patients (196,262 (34,35,73,118,153,178,228,252,258); however, other studies have reported acquisition rates of 0 to 6% (127,153,246,257). These differences in the acquisition rates of C. difficile in neonates and young children most likely represent varied degrees of environmental exposure in nurseries or transfer from the hands of hospital staff rather than disparities in the rate of maternal exposure (12).…”
Section: Introductionmentioning
confidence: 99%
“…32 The source of C. difficile in neonates is believed to be either the mother's vaginal flora or the health care environment. 33,34 In older children, day-care reservoirs for acquisition of C. difficile have been described. 35 …”
mentioning
confidence: 99%
“…20 In addition, 6 (21%) of 29 women initially presenting to a second sexually transmitted diseases clinic in the United Kingdom were also found to be colonized with C. difficile in their vaginal tracts. 21 Nevertheless, other studies have failed to confirm these findings. 22 Our patient had recently been hospitalized at an outside hospital; however, he denied receiving antibiotics or a proton pump inhibitor.…”
Section: Discussionmentioning
confidence: 85%